Optimizing Digital-Based Home Industry in Improving Digital Business in Rural Communities - Mamuaya, Nova Ch.; Ardi, Abdullah; Gunawan, Anak Agung Ngurah; Putra, Ramadhani Kirana; Yeni, Afni (Universitas Pahlawan Tuanku Tambusai, 2024)
Technological advances that are increasingly sophisticated in this modern era are one of the innovations resulting from the rapid development of technology, namely online sales or digital business. Digital Business is a training program to improve sales innovation competency aimed at company players who intend to operate on a Micro, Small and Medium Enterprise (MSME) scale or village residents who have not yet or have done so. The current development of information and digital technology has had a significant impact on various aspects of life, including the world of business and marketing. Digital transformation has influenced the way society interacts, communicates and accesses information. In the context of the development of home-based businesses in villages, the use of digital business technology is becoming increasingly relevant and important for expanding markets and increasing the competitiveness of the products and services produced. The main aim of these applications is to engage village communities. In business, people's participation can generate profits, one of which is through digital marketing. Social media is considered to have the ability to directly reach customers, because they are cheap and do not require special skills to start a business. The Community Service Team is motivated to inform other people about the use of information and communication technology because village residents do not understand what digital marketing is. The results of the community service program for villagers in the Tanjung Batu Village area, Wanea District, Manado City, North Sulawesi, had a positive impact on those who participated. This is proven by increases in knowledge, skills and product quality, number, type and turnover, management capabilities, profits and the number of new entrepreneurs.